Analysis of the plant hormone expression profile during somatic embryogenesis induction in teak (Tectona grandis) - Zhou, Wenlong; Yang, Guang; Pan, Dongkang; Wang, Xianbang; Han, Qiang; Qin, Yaqi; Li, Kunliang; Huang, Guihua (Frontiers in Plant Science, 2024)
Plant somatic embryogenesis (SE) is an efficient regeneration system for propagation. It involves the regulation of a complex molecular regulatory network encompassing endogenous hormone synthesis, metabolism, and signal transduction processes, induced through exogenous plant growth regulators.Previous studies have focused primarily on traditional propagation methods for Tectona grandis, but there is limited knowledge on SE and its hormonal regulatory mechanisms. In our study, different SE stages, including the nonembryogenic callus (NEC), embryogenic callus (EC), and globular and heart-shaped embryo (E-SEs) stages, were induced in teak cotyledons incubated on MS medium supplemented with 0.1 mg/L thidiazuron (TDZ). Morphological and histological observations indicated that EC primarily originates from the development of embryogenic cell clusters. During SE induction, the levels of six classes of endogenous hormones, IAA, CTK, ETH, ABA, SA, and JA, changed significantly. Transcriptome analysis revealed that endogenous hormones participate in SE induction in teak through various biological processes, such as biosynthesis, metabolism, and signal transduction pathways. We found that IAA biosynthesis primarily occurs through the IAM pathway during these three stages. The ETH receptor kinase gene SERF1 exhibited the highest expression levels in E-SEs. The ABA-, SA-, and JA-related signal transduction genes ABI3, NPR1, and JAZ exhibited no differential expression during different stages. Moreover, key encoding genes of SE regulators, including WUS, WOX and SERK, were differentially expressed during SE. In conclusion, this study offers insights into the roles of endogenous hormones and their interactions during SE induction.